Water War of the Mae Ta Chang Basin, Chiang Mai: Concept and Tools for Confict Management in Buddhist Perspective - Dhammahaso, Phramaha Hansa (วารสาร มจร สังคมศาสตร์ปริทรรศน์, 2013)
Water plays a very essential role in human life.' In his royal speech, King Bhumibhol says: "The important thing is we must have water for drink and agriculture. Wherever people exist, they can live if there is water. But if there is no water, they cannot live. On the contrary, if there is no electricity, one can live. If, however, there is electricity but no water, one cannot live."2 According to Ismail Serageldin, Vice President of World Bank, the war in the twentieth century resulted from the fight for oil. Yet the war in the twenty-first century will be the battle for water. In this regards, we sees the water war in several countries, for example, India , Bangladesh', Sudan, Egypt, and Kenya'. The United Nations thus warns: "In the future, there will be a water crisis which leads to more water wars on international stage.'' In the same way, the New York Times points out the issue regarding the lack of water in 'T'exas in the first year of the twenty-first century: "For 'Texas now, water has become liquid gold instead of oil.'s The expression of this issue is not an exaggeration when the severe situation of water crisis was found in 1998. It is also believed that the number is rising up to 56 countries within the year 2005. During 1990-2005, the number of population in these water crisis areas would likely increase from 131 million to 817 million. Since the initiation of the National Economic and Social Development Plan in the late 1950:, Thailand's capitalism and consumerism has expanded continually. Such expansion together with the growth of materialism results in the unbalanced condition" between man, environment, and society, which is followed by the "non-correspondence" between economics, politics, society, culture, tradition, and environment.